Evaluation of an appraisal regarding the establishment of Drug Information Service Center in the medical institution - Bavane, Dattatray Sampatrao; Ramoji, Prashanth Chary; Gursale, Santosh; Bhavsar, Rahul; Nanaware, Subhash (International Journal of Basic & Clinical Pharmacology, 2017)
Background: India has an exploding drug market in generic and brand name products with variable cost. Many doctors tend to rely on pharmaceutical representatives for their prescribing information. Now it is agreed that the major objectives of DISC are to provide a rational basis for choosing and using drugs skilfully to relieve patient’s ailments. This is becoming more and more important as the practicing doctors is now confronted with so called “newer drugs” at such a great pace that even a full- time pharmacologist sometimes finds it difficult to keep abreast of their merits and demerits. The DISC provides the knowledge of number of drugs for practical application while prescribing. To provide healthcare professionals and patients with immediate access to accurate, concise and unbiased information on drug therapy problems. Methods: This is randomized study is to be conducted to determine the opinions of doctors, medical students, nurses, patients, other non-medical staff and general public as a patient representation from our institute campus regarding necessity of drug information. They are provided written feedback forms to be filled. The drug information service center (DISC) routinely responds to queries/inquiries regarding various drug related information. A structured eleven points questionnaire containing both open and close ended questions is prepared for opinion poll in feed-back form. Results: Large majority of the health and non-health professionals of opinion poll are in favour of reforms &innovations. They also suggested their own suggestions regarding the refreshing the subjects. Conclusions: It is essential to create awareness of the services provided by the DISC among physician’s pharmacists, nurses and consumers so that they should come forward to utilize these services.